중국어 ‘수반’ 의미의 전치사 좌초 회피 현상 ― 주제화의 상황을 중심으로 - 정혜인; Chong Hyeyin (중국학보, 2024)
본 연구는 ‘동작의 수반 대상’을 나타내는 주제문 내 전치사구 보류 전략이 마치 수의적으로 허용이 되는 것처럼 보이는 현상에서 출발하였다. 표면적으로 불규칙적으로 보이는 동작의 수반 대상의 주제화 상황에 사용되는 전치사 좌초 회피 전략 이면의 규칙성을 찾고자 시도하였다. 전치사 좌초를 피하기 위해, 수반 대상이 주제화된 문장은 전치사구의 보류 전략을 취한다. 이 경우, 전치사구 보류 전략 외에도 부사 ‘一起’가 수반 의미를 나타내는 주제문에서 보조 수단으로 사용된다. ‘一起’의 사용은 술어의 특성에 따라 세 가지로 나눌 수 있다. 첫째, 교호성이 높은 술어의 주제문에서는 전치사구만 보류할 뿐 ‘一起’를 사용하지 않는다. 둘째, 교호성이 높거나 낮지 않은 술어의 주제문에서는 ‘一起’를 사용해도 되고 사용하지 않아도 무방하다. 셋째, 교호성이 낮은 주제문에서는 전치사구 보류 전략 외에 ‘一起’를 사용하여 주제와 그와 동작을 공통적으로 수행하는 참여자를 강조한다. 이러한 현상은 주제화 자체의 기능과 관련이 있다. 특히 유형III.에서 ‘一起’의 사용은 수반 대상을 포함한 주제화된 성분의 명확성을 보장하기 위한 것이다. 중국어 수반 의미가 주제화 된 문장에서 ‘一起’의 선택적 사용은 주제화 자체의 본질적인 기능, 즉 주제 자체의 범위를 명확하게 설정하며 나아가 술어의 범위까지도 명확히 한다는 목표에 부합하는 것이라고 할 수 있다. This paper originated from the irregular phenomenon founded from prepositional strnaidng avoidance strategy in a topicalized sentence representing ‘the comitative object of action’. It attempted to find the underlying regularity behind the avoidance strategy of prepositional stranding used in the topicalization situations of accompanying objects, which superficially seem irregular. To avoid prepositional stranding, sentences where the accompanying object is topicalized use the prepositional phrase retention strategy. In this case, in addition to the prepositional phrase retention strategy, the adverb ‘一起’ (yīqǐ, meaning ‘together’) is used as an auxiliary means to express accompanying meaning in the subject sentence. The use of ‘一起’ can be categorized into three types based on the characteristics of the predicate. First, in topicalized sentences with highly interactive predicates, only the prepositional phrase is retained without using ‘一起’. Second, in topicalized sentences with predicates that are neither highly interactive nor low in interactivity, ‘一起’ can be used, but it is not mandatory. Third, in topicalized sentences with low interactivity, ‘一起’ is used in addition to the prepositional phrase retention strategy to emphasize the participants who jointly perform the action along with the topic. This phenomenon is related to the function of topicalization itself. In particular, in Type III, the use of ‘一起’ serves to ensure the clarity of the topicalized component that includes the accompanying object. The optional use of ‘一起’ in sentences where the accompanying meaning is topicalized aligns with the essential function of topicalization itself, namely, to clearly establish the scope of the topic itself, further clarifying the scope of the predicate as well.